Tablet XI of the Gilgamesh Epic and the Biblical Flood Story. A Refutation of the Generally Held View that Genesis Chapters 6-9 is Based upon a Babylonian Prototype - Rapaport, I.
available from author at Herzog Street 22/5, Givatayim, Israel.